Предмет: Математика,
автор: danacoi728
(62-m)*6-39=45. уравнения
Ответы
Автор ответа:
0
Ответ:
62-m=(45+39)÷6
62-m=84÷6
62-m=14
m=62-14
m=48
(62-48)×6-39=45
Автор ответа:
0
Ответ:
Пошаговое объяснение:
(62 - m) * 6 - 39 = 45
(62 - m) * 6 = 45 + 39
(62 - m) * 6 = 84
62 - m = 84 : 6
62 - m = 14
m = 62 - 14
m = 48
Похожие вопросы
Предмет: Русский язык,
автор: Аноним
Предмет: Английский язык,
автор: jdfxafg
Предмет: Русский язык,
автор: ola1357
Предмет: Физика,
автор: Gudgirly
Предмет: История,
автор: olkaelka1